Dynamic effects of urbanization, governance, and worker's remittance on multidimensional food security: An application of a broad-spectrum approach. (December 2022) - Farrukh, Muhammad Umar; Bashir, Muhammad Khalid; Rola-Rubzen, Maria Fay; Ahmad, Ashfaq
Abstract: This study explores the synergistic causal effects of remittance inflows, urbanization, and quality of governance on multidimensional food security in Pakistan using large-scale time-series data over the period of 1973–2019. We use a broad-spectrum approach to empirically estimate temporal symmetrical relationships. The analysis revealed that utilization of worker's remittance has a significant negative impact on multidimensional food security but not on food access. Urbanization growth was also found to be negative and had a significant effect on all dimensions of food security. On the other hand, we found an overall positive relationship of governance quality, agricultural share to GDP, and government development expenditures for food availability, access, utilization, and stability. The empirical analysis suggests that utilization of remittances in a developing country such as Pakistan has the potential to negatively influence food security by decreasing the area of cropland because of non-agricultural-induced investment. To deal with this problem, scholars should collaborate across multi-disciplinary boundaries and leverage the advantages of multidimensional research design to study the effects of capital inflows and various dimensions of food security. As policymakers and researchers become aware of these complex relationships, more can be done to understand the opportunities and risks for national, household, and individual food security and sustainable development. Highlights: The "food security" issue in the context of multidimensional is a growing interest. The study examines the dynamic effects of urbanization, and quality of governance on multidimensional food security. Urbanization growth was also found to be negative on all dimensions of food security. We found an overall positive relationship of governance quality with food availability, access, nutrition, and stability. Remittances has the potential to negatively influenced multidimensional food security.